'But What to Change?': Moving Forward in Public Library Information Service Provision for People with an Invisible Disability. Issue 2 (3rd April 2017) - Muir, Bec
Abstract: This project will explore the match between public library service provision and delivery and the needs of people with invisible disabilities in Australia. A mixed method approach will be applied, utilising interviews and surveys with people with an invisible disability and library service providers.